(untitled) (Journal of Engineering, 2025)
One of the advanced techniques in enhanced oil recovery (EOR) is the miscible injection of carbon dioxide (CO2), which can both boost oil displacement and decrease the greenhouse effect. One of the most important indicators for ensuring full miscibility between two phases and optimal injection process efficiency is the Minimum Miscibility Pressure (MMP). There are many methods, such as experimental methods, that are accurate yet costly and time-consuming for determining the MMP; thus, researchers often turn to mathematical techniques, including equations of state and empirical correlations. This study aims to determine the minimum miscible pressure for CO2 in one of the Iraqi fields for its importance in determining the pressure at which CO2 injection is miscible with oil. The equation of state (EOS) was used in different ways and was compared with some correlations such as Glaso, Yelling and Metcalfe, and Lee to determine whether the equation of state is good or not. The PVT model was started, through which a regression was made between the laboratory data and the data that was calculated from EOS. Then, the MMP was evaluated in different ways. Cell to cell, key tie line, and multiple mixing, and when compared with the correlations, it was found that the multiple mixing method gave the highest error rates than the rest of the methods, while key tie line and cell to cell gave the same value of minimum miscible pressure. However, the Yelling and Metcalfe correlation gave a higher error rate than from Cell to Cell, but an acceptable rate.